2018
DOI: 10.1007/s13244-018-0642-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography: compression elastography and shear-wave elastography in the assessment of tendon injury

Abstract: Ultrasound elastography (USE) is a recent technology that has experienced major developments in the past two decades. The assessment of the main mechanical properties of tissues can be made with this technology by characterisation of their response to stress. This article reviews the two major techniques used in musculoskeletal elastography, compression elastography (CE) and shear-wave elastography (SWE), and evaluates the studies published on major electronic databases that use both techniques in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(126 citation statements)
references
References 121 publications
3
114
0
9
Order By: Relevance
“…The lack of agreed, validated SWE values for tendinopathy may currently limit its use in the assessment of tendon injury. [45] In line with previous work utilising both ultrasonography and dual energy CT, [25,[37][38][39] we have demonstrated a higher prevalence of both intra-tendinous tophi and intra-tendinous power Doppler signals in people with gout, yet limited structural damage per se. Laboratory-based studies have reported weaker foot/leg muscles in those with gout than non-gout participants.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of agreed, validated SWE values for tendinopathy may currently limit its use in the assessment of tendon injury. [45] In line with previous work utilising both ultrasonography and dual energy CT, [25,[37][38][39] we have demonstrated a higher prevalence of both intra-tendinous tophi and intra-tendinous power Doppler signals in people with gout, yet limited structural damage per se. Laboratory-based studies have reported weaker foot/leg muscles in those with gout than non-gout participants.…”
Section: Discussionsupporting
confidence: 90%
“…[52][53][54] In Achilles tendinopathy evaluation, the studies showed moderate to perfect correlation between the USE and Bmode US and excellent correlation with functional scores. 54,55 Coombes et al reported that low shear wave velocity is correlated with higher age, self-reported pain, and with decreased loading capacity of the Achilles tendon. 56 Slane et al also showed lowering shear wave speed in older adults and reported that aging alters spatial variations in the Achilles tendon.…”
Section: Tendonmentioning
confidence: 99%
“…57 Studies in athletes demonstrated that tendon softening may predict pain and tendinopathy. 55 Thus USE may prove useful in the detection of subclinical tendinopathy, and timely preventive measures may be undertaken. 55 Subclinical changes of Achilles tendon were also shown with USE in patients with ankylosing spondylitis, acromegaly, and in patients with diabetic ulcers.…”
Section: Tendonmentioning
confidence: 99%
“…However currently, the lack of agreed and validated SWE values for tendinopathy may limit its use in the formal assessment of tendon damage. [51] Previous clinical and laboratory-based studies have reported weaker foot/leg muscles in those with gout than in non-gout participants. [52,53] This muscle weakness was also associated with greater levels of foot pain.…”
Section: Discussionmentioning
confidence: 98%